O enriquecimento ambiental previne comportamentos do tipo ansioso em camundongos submetidos ao modelo de empatia pela dor - Carmona, Isabela Miranda (2023)
Empathy is the ability to share emotions, enabling the prediction and understanding of the feelings, actions, and motivations of others. In animal models, empathy can be studied through experimental protocols that investigate the behavioral reactions of conspecifics subjected to experiencing the suffering of their partners. In this context, data from our research group have shown an increase in anxiety-related behaviors in mice housed with conspecifics subjected to chronic sciatic nerve injury. These findings encouraged us to seek a non-pharmacological alternative to alleviate the impact of living with a partner experiencing chronic pain. Thus, the main objective of the present research was to analyze the effects of environmental enrichment (EE) on anxious behavior in mice exposed to the empathy for pain paradigm and tested in the elevated plus-maze (EPM). Additionally, we investigated the neuronal activation pattern of the basolateral and central nuclei of the amygdala, as well as the CA1 (cornu ammonis 1) subarea and dentate gyrus of the dorsal hippocampus. To achieve this, male Swiss mice were exposed to a 28-day cohabitation protocol. On the 21st day after birth (postnatal day; PND 21), mice were housed in pairs (observer and demonstrator) for 14 days to establish familiarity. On the 14th day (PND 35), all demonstrators underwent (constriction nerve injury demonstrator) or did not undergo (sham demonstrator) sciatic nerve constriction surgery. After this procedure, pairs were housed in either a standard environment (SE) or an environmentally enriched environment (EE). On the 28th day (PND 42), observer and demonstrator animals were exposed to the EPM. Our findings demonstrated that EE prevented the anxiogenic effect induced by the empathy for pain protocol. Furthermore, we observed that constriction nerve injury demonstrators showed increased anxiety-related responses, which were alleviated after exposure to EE. Interestingly, we noted that in constriction nerve injury demonstrators, EE significantly reduced thermal sensitivity, but did not eliminate it completely. Moreover, the constriction nerve injury condition was able to decrease activation in the dorsal hippocampus but not in the amygdala, both in the demonstrator and the observer. The data indicate that anxiety-related behaviors shared between partners were prevented in animals housed in enriched environments. This body of evidence sheds light on non-pharmacological interventions, such as adopting an environmental enrichment protocol, for managing behavioral changes, providing an effective strategy to mitigate consequences resulting from stressful contexts such as living with chronic pain.